USE OF CHLOROQUINE ON COVID-19 VIRUS INFECTION IN INDONESIA: STUDY OF LITERATURE - Ansyari, Dedi (Medicina Biomedica Journal, 2022)
BACKGROUND: COVID-19, which is caused by a new type of coronavirus, namely SARS-CoV-2, has become a disease that causes a public health emergency that is troubling the world. Chloroquine was initially reported as a potentially useful drug for COVID-19. The use of chloroquine has been reported in various countries in the world and also in Indonesia.AIM: This literature study aims to trace the use of chloroquine at the beginning of the COVID-19 pandemic until recently.METHODS: The method used is through searching articles published in national and international journals within the last 3 years.RESULTS AND CONCLUSION: From the search results, it can be concluded that chloroquine has not been proven to be useful in the management of COVID-19 patients and can cause severe side effects, its use is no longer recommended by WHO and also in Indonesia